Pengaruh Pemberian Pakan Komplit Berbasis Silase Campuran Sorgum dan Daun Gamal Dengan Konsentrat Pada Beberapa Level Terhadap Protein Kasar, TDN dan Energi Tercerna Pada Ternak Kambing Lokal Betina - Pah, Josua Alberth Williams; Yunus, Marthen; Amalo, Daud (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of the experiment was to determine the effect of complete silage-based feeding of a mixture of sorghum and gamal leaves with concentrates at different levels on crude protein, total digestibility of nutrients and digestible energy in local female goats. This experiment used 4 female local goats aged 6-8 months in the range of body weight of 11-15 kg with an average of 12.88 kg and a coefficient variation of 6.74%. The experimental method, the experimental method uses Latin Square Design (LSD) with 4 treatments and 4 periods as a repeat consisting of P0 = 80% silage + 20% concentrate, P1 = 70% silage + 30% concentrate, P2= 60% silage + 40% concentrate, P3= 50% silage + 50% concentrate. Mean crude protein (g/e/h) P0: 56.15; P1: 60.93; P2: 50.71; P3: 43.64; total nutrient digestibility (%) P0: 56.87; P1: 65.64, P2: 64.03; P3: 48.22; and digestible energy (kcal/e/h) P0: 1396.35; P1: 1521.31; P2:1231.45; P3:1063.87. The results of the variety analysis showed that the treatment had no real effect (P>0.05) on digested crude protein, TDN and digestible energy. It was concluded that the feeding of complete silage-based mixed sorghum and gamal leaves with concentrate at a ratio of 80:20 gave the same results with a higher ratio of concentrate in local female goats to digested crude protein, digested energy and TDN.